ANALYSIS AND DESIGN STRUCTURE OF BUILDING OFFICE AND ADMINISTRATIVE AL-BAHJAH CIREBON - Rama Bhakti Wibawa; Arief Firmanto (Journal of Green Science and Technology, 2019)
ABSTRACTAl-Bahjah is a formal and non-formal educational institution that combines general education with Al-Quran which is located on PangeranCakrabuana Street,Sumber, Cirebon District. The construction of Building Officeand Administration Al-Bahjah is indispensable as a center for management and administration.The planning of the Building Office and Administrative Al-Bahjah has a floor size of 30 m x 14 m with 5 floors of structure and building height of 19.60 m. The building structure is designed with reference to SNI 1727 - 2013, PPIUG 1987, SNI 2847 - 2013 and SNI 1726 - 2012.The static equivalent analysis method is used in analyzing earthquakes. The structure lies in the class of medium land sites (SD) and is included in the type D Seismic Design Category, so the earthquake force on the structure is planned using a configuration of the structure of the Special Moment Resisting Frame (SMRF).ETABS v9.6 structure analysis program is used to help structure modeling and calculate internal forces acting on the structure, with the material used is concrete f'c 25 Mpa, reinforcementfy 400 Mpa and fy 240 Mpa.Keyword: SNI 1727-2013, PPIUG 1987, SNI 2847-2013, SNI 1726-2013, Seismic Design Category D,Lateral Equivalent Analysis, SMRF, ETABS v9.6.0